2016
DOI: 10.1002/1873-3468.12429
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the mouse protein phosphatase ppm1l gene leads to structural abnormalities in the brain

Abstract: PPM1L, a member of the metal-dependent protein phosphatase (PPM) family, is involved in regulating the stress-activated protein kinase pathway and ceramide trafficking. However, the physiological function of PPM1L in the brain is unclear. In this study, we generated and analyzed ppm1l-deficient mice in order to investigate PPM1L functions in the brain. Our results indicate that ppm1l is highly expressed in the central nervous system during mouse development and that ppm1l mice display impaired motor performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Accumulating evidence has revealed that Rgs14 may negatively regulates the capacity of learning and memory in the CA2 region of the hippocampus by integrating G protein and ERK/MAPK signaling. [20][21][22][23][24] Furthermore, some researchers demonstrated Rgs14 knockout (KO) rats possess an unusually robust capacity for long-term potentiation (LTP) in CA2, which is absent in wild-type (WT) rats, and markedly enhanced spatial learning [19]. Taken together, these results show that Rgs14 acts as a critical factor for hippocampal based learning and memory and it belongs to a negative regulator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has revealed that Rgs14 may negatively regulates the capacity of learning and memory in the CA2 region of the hippocampus by integrating G protein and ERK/MAPK signaling. [20][21][22][23][24] Furthermore, some researchers demonstrated Rgs14 knockout (KO) rats possess an unusually robust capacity for long-term potentiation (LTP) in CA2, which is absent in wild-type (WT) rats, and markedly enhanced spatial learning [19]. Taken together, these results show that Rgs14 acts as a critical factor for hippocampal based learning and memory and it belongs to a negative regulator.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that Ppm1l inhibited in ammatory responses by directly dephosphorylating IKKβ and suppressing NF-κB activation in cardiac macrophages, subsequently prevented excessive scar formation and improved cardiac function [20]. Moreover, it was reported that Ppm1l was highly expressed in the central nervous system during mouse development and played an important role in brain development [21]. To date, Ppm1l should be discovered and reported by proteomics techniques in mitochondrial hippocampus for the rst time.…”
Section: Discussionmentioning
confidence: 99%
“…We found 15 genes associated with lineage-specific accelerated regions in the common ancestor of the great apes which showed particularly high expression in the human fetal brain (Fig. S27 and table S31) (P = 0.023, Modified Fisher's Exact test); over half of these genes have been reported to have roles in brain development and function (102)(103)(104)(105)(106)(107)(108)(109). For example, knockout of the transcription factor-encoding MEF2C in a mouse model results in impaired neuronal differentiation and smaller somal size among neural progenitor cells (108).…”
Section: Brain Evolutionmentioning
confidence: 99%